Editorial - Gonzales Muñiz, Nelly L. (2019)
Nowadays it is essential to understand that the search for solutions to possible problems is acquiring knowledge through the interaction between the different actors and contexts that surround us, through research we can understand, analyze, diagnose and propose possible solutions to improve human life .We must not forget that the University is the right space to foster these capacities, hence teachers must motivate and interact with our peers and students not only in training activities but also in research activities, to develop and innovate our creative thinking in a way ethically and correctly, but at the same time act in a thoughtful, systematic and methodical way.The Faculty of Architecture and Urbanism of the Universidad Privada de Tacna, as a form of science communication, has as one of its objectives as of 2006, to reach the magazine "ARQUITEK" initially as an academic magazine and from the year 2013 as a scientific journal, indexed in LATINDEX, for two years with semi-annual edition and multidisciplinary content. With special effort we offer readers “ARQUITEK 2019” in its 15 edition with articles of great scientific quality, whose authorship is the result of the practice of the scientific method with conclusions that allow us to understand with clarity what was found in a wayobjective in each of the investigations, in the same way our recognition to the Editorial Committee, to the External Evaluators, to all those who contributed in this important work and especially to the authors of the articles for their generous contribution:• Cesar Fortunato Martínez Vítor.• Silvia Noelia López Ortega.• Alfonso Oswaldo Flores Mello.• Roger Aníbal Romo Rojas.• Lenin John Meléndez Rodríguez.• Nahuel Humberto Molero Yáñez.• Eduardo Alonso Romero RamírezI conclude by highlighting that our scientific magazine “ARQUITEK 2019”, seeks national and international prestige, hence its mass dissemination, so that the data recorded in its content, can be fundamental platforms for information search for scientific research.